Development of a Symptom‐Focused Patient‐Reported Outcome Measure for Functional Dyspepsia: The Functional Dyspepsia Symptom Diary (FDSD). (January 2018) - Taylor, Fiona; Higgins, Sophie; Carson, Robyn T; Eremenco, Sonya; Foley, Catherine; Lacy, Brian E; Parkman, Henry P; Reasner, David S; Shields, Alan L; Tack, Jan; Talley, Nicholas J
Abstract : OBJECTIVES: The Functional Dyspepsia Symptom Diary (FDSD) was developed to address the lack of symptom‐focused, patient‐reported outcome (PRO) measures designed for use in functional dyspepsia (FD) patients and meeting Food and Drug Administration recommendations for PRO instrument development. METHODS: Concept elicitation interviews were conducted with FD participants to identify symptoms important and relevant to FD patients. A preliminary version of the FDSD was constructed, then completed by FD participants on an electronic device in cognitive interviews to evaluate the readability, comprehensibility, relevance, and comprehensiveness of the FDSD, and to preliminarily evaluate its measurement properties. RESULTS: During concept elicitation interviews, 45 participants spontaneously reported 19 symptom concepts. Of those, seven symptoms were selected for assessment by the eight‐item FDSD. Cognitive interviews with 57 participants confirmed that participants were able to comprehend and provide meaningful responses to the FDSD, and that the handheld electronic FDSD format was suitable for use in the target population. Scores of the FDSD were well‐distributed among response options, item discrimination indices suggested that the FDSD items differentiate among patients with varying degrees of FD severity, and inter‐item correlations suggested that no items of the FDSD were capturing redundant information. Internal consistency estimates (0.87) and construct‐related validity estimates using known‐groups methods were within acceptable ranges. CONCLUSIONS: The FDSD is a content‐valid PRO measure, with preliminary psychometric evidence providing support for the FDSD's items and total score. Further psychometric evaluations are recommended to more fully test the FDSD's score performance and other measurement properties in the target patient population.